Rhapsodies Hongroises pou Piano: Vol.I, Vol. II (66 + 71) - LISZT, F. (Schlesinger\'sche Buchu-u Musikhandlung)
Di dalam buku ini terdapat 2 volume lagu. Volume I: A.E. Zerdahely; Au Comte Ladislas Teleky; Au Comte Leo Festetics; Au Comte Casimir Esterhazy; A Midmela Contesse Sid. Reviczky; Au Comte Antoine D'Appony. Volume II: Au Baron Fery Orczy; Au Baron Fery Orczy; A.J. Joachim; Au Comte Leo Festetics; A.H.G. de Bulow; Rakoczy-Marche.